(untitled) (ModaPalavra e-periódico, 2025)
This paper’s goal is to comprehend the social representations concerning the attribution of gender to clothing. To that end, a sample of 256 people answered a word association test (Teste de Associação Livre de Palavras – TALP) with stimulus words such as “roupa masculina” and “roupa feminina” (men’s and women’s clothes, respectively). The data have been analyzed through Prototypical Analysis, via Iramuteq software. Results indicate, for “roupa masculina”, words exhibit higher practicality, comfort and sobriety. As for “roupa feminina”, words denote greater clothing variability as well as a focus on aesthetic aspects through colors and prints. In conclusion, social representations, along with stereotypical attribution regarding clothing and gender, are still based on a gender binary rationale that assigns the behavioral code and the dress code to individuals.